Environmental photochemistry of dienogest: phototransformation to estrogenic products and increased environmental persistence via reversible photohydration. Issue 11 (16th October 2017) - Pflug, Nicholas C.; Hankard, Madeline K.; Berg, Stephanie M.; O'Connor, Meghan; Gloer, James B.; Kolodziej, Edward P.; Cwiertny, David M.; Wammer, Kristine H.
Abstract : Reversible photohydration of dienogest also yields estrogenic byproducts. Abstract : Potent trienone and dienone steroid hormones undergo a coupled photohydration (in light)-thermal dehydration (in dark) cycle that ultimately increases their environmental persistence. Here, we studied the photolysis of dienogest, a dienone progestin prescribed as a next-generation oral contraceptive, and used high resolution mass spectrometry and both 1D and 2D nuclear magnetic resonance spectroscopy to identify its phototransformation products. Dienogest undergoes rapid direct photolysis ( t 1/2 ∼ 1–10 min), forming complex photoproduct mixtures across the pH range examined (pH 2 to 7). Identified products include three photohydrates that account for ∼80% of the converted mass at pH 7 and revert back to parent dienogest in the absence of light. Notably, we also identified two estrogenic compounds produced via the A-ring aromatization of dienogest, evidence for a photochemically-induced increase in estrogenic activity in product mixtures. These results imply that dienogest will undergo complete and facile photolytic transformation in sunlit surface water, yet exhibit greater environmental persistence than might be anticipated by inspection of kinetic rates. Photoproduct mixtures also include transformation products with different nuclear receptor binding capabilities than the parent compound dienogest. These outcomes reveal a dynamic fate and biological risk profile for dienogest that must also take into account the composition and endocrine activity of its transformation products. Collectively, this study further illustrates the need for more holistic regulatory, risk assessment, and monitoring approaches for high potency synthetic pharmaceuticals and their bioactive transformation products.